Regional Developments of General Stylistic Trends in the Palaeologan Architecture of Aegean Macedonia - Zavorina, Maria L. (Actual Problems of Theory and History of Art, 2023)
The article presents the experience of analyzing of Palaeologan architecture as a flexible system. An attempt is made to trace the specifics of the development of the Palaeologan style over time in the aspect of the issue of regional developments in the Late Byzantine Architecture on the example of Aegean Macedonia. At the late 13th–14th centuries several regional centers became active here — Thessaloniki, Mount Athos, Veria and Kastoria, each of them formed its own idiosyncratic architectural variant in line with general stylistic trends of the period. Based on the analysis of style-forming components — i.e. morphological properties, proportions, spatial solutions, articulation and decoration of facades, general and particular compositional features of monuments — as well as relying on the historiographic characteristics of the Palaeologan style, the characteristics of its regional architectural interpretations are given, and particular trends of their development are identified.This research was funded by the Russian Scientific Fund, project 20-18-00294 “Artistic Traditions, Church and State Ideology in the Medieval Architecture and Art of the Balkans: Macedonian Issue”.
Keywords: Byzantine architecture; Palaeologan era; style; Macedonia; Thessaloniki; Veria; Kastoria; Athos